2021
DOI: 10.1016/j.cegh.2020.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Is BCG associated with reduced incidence of COVID-19? A meta-regression of global data from 160 countries

Abstract: Background Global research is running towards to find a vaccine to stop the threat of the COVID-19. The Bacillus Calmette–Guérin (BCG) vaccine that prevents severe forms of tuberculosis is getting more attention in this scenario. The objective of our study was to determine the association between BCG vaccine coverage and incidence of COVID-19 at a national-level across the Globe. Methods The data of 160 countries were included in the study. Meta-regression was done to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 6 publications
0
24
0
1
Order By: Relevance
“…Accordingly, there is a hypothesis that the substantial differences may be related to the universal BCG vaccination policies of these countries. Several ecological studies analyzed worldwide data before June 2020 and found that even after controlling for important country level factors such as temperature, total population size, population density, proportion of those aged 60 years or above, gross domestic product per capita, healthcare access and quality measures, COVID-19 testing numbers, and stringency level of the nationwide epidemic control policy, the BCG vaccination coverage rate and the total BCG vaccination implementation years among these countries are still significantly inversely correlated with the incidence and mortality of COVID-19 [5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, there is a hypothesis that the substantial differences may be related to the universal BCG vaccination policies of these countries. Several ecological studies analyzed worldwide data before June 2020 and found that even after controlling for important country level factors such as temperature, total population size, population density, proportion of those aged 60 years or above, gross domestic product per capita, healthcare access and quality measures, COVID-19 testing numbers, and stringency level of the nationwide epidemic control policy, the BCG vaccination coverage rate and the total BCG vaccination implementation years among these countries are still significantly inversely correlated with the incidence and mortality of COVID-19 [5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Whether BCG vaccination could have a beneficial effect against COVID-19 also under intense debate. Several ecological studies did suggest the potential protective effect of the universal BCG vaccination program on reducing COVID-19 morbidity and mortality [5][6][7][8][9][10][11][12][13]; some also implied that different BCG strains might vary in their protective ability [14]. In contrast, the inverse relation between COVID-19 disease burden and BCG vaccination was not observed by others [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…With the ongoing COVID-19 pandemic, there have been reports that patients who are BCG-vaccinated are less susceptible to serious illness and have less severe COVID-19 symptoms [ 82 ]. Several studies are currently being conducted worldwide to determine whether BCG vaccination has a protective effect against COVID-19 ( #–NCT04537663, NCT04379336, NCT04369794, NCT04461379, NCT04347876) [ 82 , 83 , 84 , 85 ]. These studies indicate that the immunologic SNP panel could also be utilized as an important tool if BCG is preventative or can reduce the pathogenicity of COVID-19 as well as other infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…who.int/teams/global-tuberculosis-programme/covid-19) dringend empfohlen. Epidemiologische Daten führten zu der Hypothese, dass durch die Tuberkuloseimpfung (BCG) ein Schutz gegen SARS-CoV-2-Infektionen und deren schwere Verläufe entstehen könnte [118,120]. Eine heterologe Schutzwirkung gegen andere Virusinfektionen wurde zwar beschrieben [121], ob diese auch für SARS-CoV-2 angenommen werden kann, ist bislang nicht bewiesen und wird aktuell in Studien geprüft.…”
Section: Epidemiologie Schwerer Verläufeunclassified